Robot Intelligence Technology and Applications 5 Results from the 5th International Conference on Robot Intelligence Technology and Applications - Kim, Jong-Hwan.; Myung, Hyun.; Kim, Junmo; Xu, Weiliang; Matson, Eric T.; Jung, Jin-Woo.; Choi, Han-Lim.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes papers from the 5th International Conference on Robot Intelligence Technology and Applications held at KAIST, Daejeon, Korea on December 13-15, 2017. It covers the following areas: artificial intelligence, autonomous robot navigation, intelligent robot system design, intelligent sensing and control, and machine vision. The topics included in this book are deep learning, deep neural networks, image understanding, natural language processing, speech/voice/text recognition, reasoning & inference, sensor integration/fusion/perception, multisensor data fusion, navigation/SLAM/localization, distributed intelligent algorithms and techniques, ubiquitous computing, digital creatures, intelligent agents, computer vision, virtual/augmented reality, surveillance, pattern recognition, gesture recognition, fingerprint recognition, animation and virtual characters, and emerging applications. This book is a valuable resource for robotics scientists, computerscientists, artificial intelligence researchers and professionals in universities, research institutes and laboratories.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Artificial intelligence; Computational Intelligence; Control, Robotics, Automation; Artificial Intelligence